(untitled) (Indonesian Health Justice Review, 2024)
As Indonesia’s elderly population grows, ensuring health justice for older adults becomes increasingly crucial. This study examines the healthcare gaps faced by older Indonesians, particularly in terms of accessibility, affordability, and quality of care. The research utilizes a mixed-methods approach, including surveys of elderly individuals and healthcare providers, as well as a review of national health policies related to aging. Findings reveal significant disparities in healthcare access, with elderly populations, particularly those in rural areas, often facing limited access to specialized care, inadequate financial support, and social isolation. While Indonesia’s Universal Health Coverage (UHC) program aims to provide broad access to healthcare, elderly individuals are frequently excluded from key services, including long-term care and geriatric health services. The paper argues that Indonesia’s healthcare system must adapt to the specific needs of older adults by improving access to geriatric care, providing better financial protection, and addressing social determinants of health. The study concludes with recommendations for policy reforms, including the integration of geriatric care into the UHC framework and enhanced training for healthcare professionals to cater to the aging population.